The Quran's Views In Responding To Disinformation: Implications And Strategies In The Post-Truth Era - Mumtaz Muizza, Muhammad Ahmad; Permatasari, Murnia Andini; Luthfi, Hikmatul (Modern Islamic Studies and Sharia Research, 2025)
This article discusses the Qur'an's views on disinformation and strategies that can be applied in dealing with this phenomenon in the post-truth era. In a context where information spreads quickly and often without verification, disinformation poses a significant challenge that can undermine social integrity and public trust. Using a qualitative approach and text analysis, this study explores terms in the Qur'an related to lies and deception, as well as emphasizing the importance of honesty and verification of information. Through the analysis of the verses related to this discussion, it was found that the Qur'an provides relevant ethical guidelines for dealing with disinformation. This study shows that a critical and selective attitude in receiving and disseminating news is very important, with an emphasis on tabayyun (verification) to avoid regret due to misinformation. The implications of these findings confirm that the principles of the Qur'an can serve as a moral guide in dealing with disinformation in the digital age, as well as contribute to people's efforts to strengthen social harmony and integrity.